PEMBUATAN DAN PEMANFAATAN MADING SEKOLAH SEBAGAI SARANA LITERASI, KREATIVITAS DAN KOMUNIKASI DI SEKOLAH DASAR - Arman, Diah Mulyani; Aprilia, Nur Afiqoh; Sabihisma, Septa; Malentika, Nella; Indryani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the process of developing and utilizing school wall magazines (mading) as a medium for literacy, learning, and creativity enhancement among students at SDN 66/IV Kota Jambi. Using a descriptive qualitative method, the research involved the principal, supervising teachers, mading coordinators, and participating students selected purposively. Data were collected through observation, interviews, and documentation, and analyzed through data reduction, data display, and conclusion drawing. The findings indicate that mading management follows a structured process consisting of planning, content production, installation, and maintenance. The wall magazine serves as an integrated instructional tool, a supporting medium for school literacy programs, and an effective channel of communication within the school environment. Active student participation in content creation enhances reading interest, writing skills, creativity, collaboration, and self-confidence. However, several challenges remain, including limited time, inadequate facilities, and fluctuating student involvement. Strengthening management systems, providing training in writing and visual design, and adopting digital mading platforms are recommended to ensure sustainability. Overall, mading demonstrates significant potential as a cost-effective educational medium that promotes literacy, creativity, and positive school culture.